EFFICIENCY OF INTRODUCTION OF WATER-SAVING IRRIGATION TECHNOLOGIES TO IMPROVE WATER USE IN THE FERGHANA VALLEY (Scientific journal of the Fergana State University, 2023)
The article analyzes the advantages of water-saving irrigation technologies in improving water use in Uzbekistan, especially in the Fergana Valley, over the years of independence, in particular, the advantages of drip irrigation over other irrigation methods, based on primary sources and scientific literature.The Ministry of Water Resources also analyzed the development of government policy in the field of water resources, the priorities for the introduction and development of new technologies in the field of water resources. The Naryn-Syrdarya Irrigation Systems Basin Department highlights the importance of establishing effective research units to improve on-farm water use to develop policies and measures for watershed organizations to conserve water in all areas and improve water quality